Numerical Analysis of a Rotor-Bearing System Supported by Elastomeric Dampers - Caetano Thomazi, Cleber; Braga dos Santos, Marcelo; Paulo Lépore Neto, Francisco (Científic@ - Multidisciplinary Journal, 2017)
Abstract In the present work, the dynamic behavior of a flexible rotor supported by fluid film journal bearings with additional damping provided by elastomers is studied. The damping devices are introduced between the bearings and their housings. The finite element method is used to model the system. The viscoelasticity is implemented through the use of Prony series. The influence of the viscoelastic properties and the dimensions of the elastomeric damper on the synchronous response are discussed. It is verified that the viscoelastic dampers may be good alternatives in the mitigation of dynamic problems inherent of high-speed and light-weight rotating machinery. Keywords: rotordynamics, fluid film bearings, viscoelastic dampers. Resumo Neste trabalho é apresentado o estudo do comportamento dinâmico de um rotor flexível suportado por mancais de filme fluido com amortecimento adicional fornecido por elastômeros. Os dispositivos de amortecimento são introduzidos entre os mancais e seus alojamentos. O método de elementos finitos é usado para modelar o sistema. A viscoelasticidade é implementada através de série de Prony. Discute-se a influência das propriedades viscoelásticas e das dimensões do amortecedor elastomérico sobre a resposta ao desbalanceamento. Verifica-se que os amortecedores viscoelásticos podem ser boas alternativas na mitigação de problemas dinâmicos inerentes às máquinas rotativas supercríticas. Palavras-chave: dinâmica de rotores, mancais de filme fluido, amortecedores viscoelásticos.